Assessment and Estimating Groundwater Vulnerability to Pollution Using a Modified DRASTIC and GODS Models (Case Study: Malayer Plain of Iran) - Maryam Hosseini; Ali Saremi (Civil Engineering Journal, 2018)
This study deals with the intrinsic vulnerability of groundwater reservoirs to pollution, by the use of two models DRASTIC and GODS, this study is done by taking samples from 17 water resources of Malayer plain Aquifer area of southern Hamedan Province, Iran. 30 physicochemical parameters and heavy metals have been studied and vulnerability of this aquifer to the nitrate concentration, was determined. The study showed that results from DRASTIC were better than GODS in Assessment and Estimating groundwater vulnerability to pollution, also DRASTIC model has been corrected, and compared the ability of these two models in vulnerability zoning has been evaluated. According to high correlation between DRASTIC index and nitrate concentration, ranking and weighting of nitrate pollutant is inserted in the DRASTIC equation, and zoning map of DRASTIC method has been calibrated by nitrate concentration. By this method, vulnerability zoning is determined between very low to very high, which shows the increase of DRASTIC index by nitrate concentration. DRASTIC parameters uncertainty has affected the zoning results in this method, but its calibration with nitrate concentration, gives more accurate vulnerability results.